Injury from electric scooters in Copenhagen: a retrospective cohort study. Issue 12 (22nd December 2019) - Blomberg, Stig Nikolaj Fasmer; Rosenkrantz, Oscar Carl Moeller; Lippert, Freddy; Collatz Christensen, Helle
Abstract : Objective: To analyse injuries related to manual and electric scooter use from January 2016 up to and including July 2019. Setting: Electric scooter rental services were launched in Denmark in January 2019. The services were provided by private companies. Although rules for handling and riding scooters have been established, no reports either before or after introduction of electric scooters anticipated the full extent of use, and injuries to riders and pedestrians. Participants: All patient records mentioning manual or electric scooters. Records were reviewed, and data were stratified according to two groups: manual and electric scooters. Interventions: A predefined survey was completed in all cases where 'scooter' was present. This contained variables such as type of scooter, type of participant, mechanism of injury, acuity, intoxication, referral to treatment facility. Outcome measures: Among incidents involving scooters, summary statistics on continuous and categorical variables of interest were reported. Results: 468 scooter-related injuries were recorded. We found that manual scooter riders were more likely to be children under the age of 15; fall alone—involving no other party; sustain contusions, sprains and lacerations; and bruise either their fingers or toes. Riders of electric scooters were likely to be 18–25 years, sustain facial bruising and lacerations requiring sutures, and be under the influence of alcohol or drugs. Non-riders of electric scooters were mostly elderly people who tripped over scooters, consequently sustaining moderate to severe injuries. Conclusion: There were two different types of population sustaining injuries from manual and electric scooters, respectively. The proportion of non-riders injured by electric scooters were surprisingly large (17%), and while electric scooters are here to stay, several apparently preventable injuries occur as a result of reckless driving and discarded electric scooters. Current rules for usage might not prevent unnecessary accidents and secure traffic safety and the lives of older individuals.